Complete Response With Cetuximab-Based Treatment of Metastatic Colorectal Cancers: Two Case Reports and Literature Review - Wei, Li; Lin, Zexiao; Xie, Sidong; Ruan, Danyun; Jiang, Wen; Cui, Yueli; Liu, Sisi; Wang, Tiantian; Chen, Zhanhong; Lin, Qu (Frontiers in Oncology, 2022)
Metastases typically develop before diagnosis and during the treatment of colorectal cancers, while patients with metastatic colorectal cancers (mCRCs) currently have a poor prognosis. In terms of surgical approaches, adjuvant therapies and targeted therapies, the treatment of mCRCs has had numerous recent advances. As a targeted agent widely used in mCRCs, cetuximab-based treatment is still under dispute due to its side effects and unstable effect. We present two mCRC cases treated with cetuximab-based therapy, of which two patients achieved complete response and without recurrence for over 22 and 84 months, respectively. To better understand the drug usage, we also reviewed the recent achievements and usage precautions of cetuximab in mCRCs. Present and many previous observations support cetuximab might be a referred drug in the first-line chemotherapy of mCRCs with wildtype RAS and BRAF, and proficient mismatch repair.